IMPLEMENTASI PERATURAN MENTERI DALAM NEGERI NOMOR 4 TAHUN 2010 TENTANG PELAYANAN ADMINISTRASI TERPADU KECAMATAN (PATEN) DI KECAMATAN MULAK ULU KABUPATEN LAHAT - Purnawan, Heru; Noviyanto, Hernowo; Tauran, Tauran (Faculty of Social and Political Sciences Universitas Prof Dr Hazairin, SH, 2022)
The District Integrated Administrative Services (PATEN) aims to improve administrative services to the community. Based on the Regulation of the Minister of Home Affairs Number 4 of 2010 concerning Guidelines for Integrated District Administration Services (PATEN) that the conditions that must be met to organize a PATEN are: Substantive requirements, namely the delegation of part of the authority of the Regent / Mayor to the Head of the District Administrative requirements which include service standards and job descriptions of sub-district personnel, and technical requirements which include facilities and infrastructure, as well as technical implementers. This study examines the implementation of PATEN in the Mulak Ulu sub-district, Lahat Regency. This study uses qualitative research methods with data collection techniques through interviews, observations, and document studies. This study shows the lack of commitment from district agencies to the delegation of authority in the Mulak Ulu district, the lack of support for facilities and infrastructure, and no budget support for the provision of facilities and infrastructure as well as the operational budget. One of the factors that influence the implementation of one-stop administrative services in Mulak Ulu District, Lahat Regency is the lack of readiness of the district government to succeed in the implementation of PATEN.